School Street, 1906 - Unknown (Tufts Archival Research Center, 2005)
Elevated-view west of School Street from City Hall Avenue. Buildings line both the north and south sides of the street. The southern grounds of City Hall are visible in the lower right corner of the photograph. The east elevation of Kings Chapel, located on the northeast corner of Tremont and School Streets, is included along the center-right side of the photograph. The Albion Building, located on the northwest corner of School and Tremont Streets, is visible in the upper-left portion of the photograph, to the west or behind King's Chapel. Awnings and signage adorn several buildings. Street lamps line the sidewalk along School Street, which is filled with horse-drawn wagons and carriages. Several pedestrians are included in the photograph. Copyright held by Detroit Publishing Company 4 5/8 x 3 1/8, 5 x 3 1/2 overall Photographs